Quantitative and qualitative differences in the activation of a fibroblast growth factor receptor by different FGF ligands - Krzyscik, Mateusz A; Karl, Kelly; Dudeja, Pooja; Krejci, Pavel; Hristova, Kalina (Cytokine & growth factor reviews, 2024)
The FGF system is the most complex of all receptor tyrosine kinase signaling networks with 18 FGF ligands and four FGFRs that deliver morphogenic signals to pattern most embryonic structures. Even when a single FGFR is expressed in the tissue, different FGFs can trigger dramatically different biological responses via this receptor. Here we show both quantitative and qualitative differences in the signaling of one of the FGF receptors, FGFR1c, in response to different FGFs. We provide an overview of the recent discovery that FGFs engage in biased signaling via FGFR1c. We discuss the concept of ligand bias, which represents qualitative differences in signaling as it is a measure of differential ligand preferences for different downstream responses. We show how FGF ligand bias manifests in functional data in cultured chondrocyte cells. We argue that FGF-ligand bias contributes substantially to FGF-driven developmental processes, along with known differences in FGF expression levels, FGF-FGFR binding coefficients and differences in FGF stability in vivo.
Keywords: ligandy; receptory fibroblastových růstových faktorů; Chondrocytes; fibroblastové růstové faktory; Receptor, Fibroblast Growth Factor, Type 1; signální transdukce; Ligands; Signaling; Signal Transduction; receptor fibroblastových růstových faktorů, typ 1; FGFR; Animals; lidé; chondrocyty; Humans; Receptors, Fibroblast Growth Factor; zvířata; Bias; FGF; Fibroblast Growth Factors